Hukum & kuasa konstitusi. Catatan-catatan untuk pembahasan rancangan undang-undang makamah konstitusi - [Tidak Terdaftar] (KRHN, 2004)
Hukum & kuasa konstitusi. Catatan-catatan untuk pembahasan rancangan undang-und..